Redox imbalance in patients with heart failure and ICD/CRT-D intervention. Can it be an underappreciated and overlooked arrhythmogenic factor? A first preliminary clinical study - Szyller, Jakub; Antoniak, Radosław; Wadowska, Katarzyna; Bil-Lula, Iwona; Hrymniak, Bruno; Banasiak, Waldemar; Jagielski, Dariusz (Frontiers in Physiology, 2023)
Introduction. Redox imbalance and oxidative stress are involved in the pathogenesis of arrhythmias. They also play a significant role in pathogenesis of heart failure (HF). In patients with HF and implanted cardioverter-defibrillator (ICD) or cardiac resynchronization therapy defibrillator (CRT-D), the direct current shocks may be responsible for additional redox disturbances and additionally increase arrhythmia risk. However, the precise role of oxidative stress in potentially fatal arrhythmias and shock induction remains unclear. Methods. 36 patients with diagnosed HF and implanted ICD/CRT-D were included in this study. Patients were qualified to the study group in case of registered ventricular arrhythmia and adequate ICD/CRT-D intervention. The control group consisted of patients without arrhythmia with elective replacement indicator (ERI) status.Activity of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione (GSH) in erythrocyte (RBC), SOD, GPx activity and reactive oxygen/nitrogen species (ROS/RNS) concentration in plasma were determined. The values were correlated with glucose, TSH, uric acid, Mg and ion concentrations. Results. In the perishock period, we found a significant decrease in RBC and extracellular (EC) SOD and RBC CAT activity (p=0.0110, p=0.0055 and p=0.0002, respectively). EC GPx activity was also lower (p=0.0313). In all patients, a decrease in the concentration of all forms of glutathione was observed compared to the ERI group. Important association between ROS/RNS and GSH, Mg, TSH and uric acid was shown. A relationship between the activity of GSH and antioxidant enzymes was found. Furthermore, an association between oxidative stress and ionic imbalance has also been demonstrated. The patients had an unchanged de Haan antioxidant ratio and glutathione redox potential. Conclusions. Here we show significant redox disturbances in patients with HF and ICD/CRT-D interventions. Oxidative stress may be an additional risk factor for the development of arrhythmia in patients with HF. The detailed role of oxidative stress in ventricular arrhythmias requires further research already undertaken by our team.